2009
DOI: 10.1016/j.phytochem.2009.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Antimalarial sesquiterpene lactones from Distephanus angulifolius

Abstract: Combined use of bioassay-guided fractionation based on in vitro antiplasmodial assay and dereplication based on HPLC-PDA-MS-SPE-NMR led to isolation of (6S,7R,8S)-14-acetoxy-8-[2-hydroxymethylacrylat]-15-helianga-1(10),4,11(13)-trien-15-al-6,12-olid and (5R,6R,7R,8S,10S)-14-acetoxy-8-[2-hydroxymethylacrylat]-elema-1,3,11(13)-trien-15-al-6,12-olid, along with vernodalol, vernodalin, and 11,13beta-dihydroxyvernodalin from extract of Distephanus angulifolius. All compounds were identified by spectroscopic methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 43 publications
(46 reference statements)
2
28
0
Order By: Relevance
“…The most active extract was that of the leaves of V. amygdalina, but in this case a strong cytotoxicity was observed on the two cell lines (KB and MRC5) at 10 g/mL and this may account for the antiplasmodial activity against P. falciparum. Vernangulides A and B, two sesquiterpene lactones, have been previously isolated from this plant and described to be responsible for the antiplasmodial activity (IC 50 of 2 g/mL), nevertheless their selectivity index is very low (from 2 to 5.3) (Pedersen et al, 2009). The leaves extract of Markhamia lutea showed 71% inhibition of P. falciparum at 10 g/mL, a significant activity was assigned to some of the cycloartane triterpenes which showed antiparasitical activity not only against P. falciparum, but also Leishmania donovani and Trypanosoma brucei (Lacroix et al, 2009).…”
Section: Scientific Namementioning
confidence: 99%
“…The most active extract was that of the leaves of V. amygdalina, but in this case a strong cytotoxicity was observed on the two cell lines (KB and MRC5) at 10 g/mL and this may account for the antiplasmodial activity against P. falciparum. Vernangulides A and B, two sesquiterpene lactones, have been previously isolated from this plant and described to be responsible for the antiplasmodial activity (IC 50 of 2 g/mL), nevertheless their selectivity index is very low (from 2 to 5.3) (Pedersen et al, 2009). The leaves extract of Markhamia lutea showed 71% inhibition of P. falciparum at 10 g/mL, a significant activity was assigned to some of the cycloartane triterpenes which showed antiparasitical activity not only against P. falciparum, but also Leishmania donovani and Trypanosoma brucei (Lacroix et al, 2009).…”
Section: Scientific Namementioning
confidence: 99%
“…A major bottleneck in our ongoing search for antiparasitic constituents from plants (Sairafianpour et al, 2002; Ziegler et al, 2002; Pedersen et al, 2009) has been the traditional time-consuming bioassay-guided isolation of the antileishmanial compounds. This urged us to implement new bioanalytical technologies for faster analyses targeting the bioactive constituents.…”
Section: Introductionmentioning
confidence: 99%
“…This technique has been employed in the identification of alkaloids from Lobelia siphilitica and Hippobroma longiflora (Campanulaceae) and sesquiterpene lactones from Distephanus angulifolius (Asteraceae) [83,84]. Another interesting study has demonstrated its use for the identification of iridoid and caffeoyl glycosides from Pinguicula lusitanica (Lentibulariaceae) [89].…”
Section: Application Of Online and At-line Lc-nmr Methods For Dereplimentioning
confidence: 99%